Successful Conservative Management of Neonatal MRSA Associated Tricuspid Valve Infective Endocarditis - Sodhi, MK; Chhabra, GS; Sarin, SS (Journal of Nepal Paediatric Society, 2013)
Prognosis in neonatal endocarditis depends on early diagnosis and the status of the patient at the time of diagnosis, and effective treatment with appropriate antibiotics. The current case report describes a case of successful conservative treatment of endocarditis in a 26 day old male neonate, previously inadequately treated for septicaemia in another hospital. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7045 J Nepal Paediatr Soc. 2013;33(1):70-73